Transition structures and timing of transfer from paediatric to adult-based care after kidney transplantation in Germany: a qualitative study. Issue 6 (12th June 2017) - Prüfe, Jenny; Dierks, Marie-Luise; Bethe, Dirk; Oldhafer, Martina; Müther, Silvia; Thumfart, Julia; Feldkötter, Markus; Büscher, Anja; Sauerstein, Katja; Hansen, Matthias; Pohl, Martin; Drube, Jens; et al.
Abstract : Objectives: It is known that transition, as a shift of care, marks a vulnerable phase in the adolescents' lives with an increased risk for non-adherence and allograft failure. Still, the transition process of adolescents and young adults living with a kidney transplant in Germany is not well defined. The present research aims to assess transition-relevant structures for this group of young people. Special attention is paid to the timing of the process. Setting: In an observational study, we visited 21 departments of paediatric nephrology in Germany. Participants were doctors (n=19), nurses (n=14) and psychosocial staff (n=16) who were responsible for transition in the relevant centres. Structural elements were surveyed using a short questionnaire. The experiential viewpoint was collected by interviews which were transcribedverbatim before thematic analysis was performed. Results: This study highlights that professionals working within paediatric nephrology in Germany are well aware of the importance of successful transition. Key elements of transitional care are well understood and mutually agreed on. Nonetheless, implementation within daily routine seems challenging, and the absence of written, structured procedures may hamper successful transition. Conclusions: While professionals aim for an individual timing of transfer based on medical, social, emotional and structural aspects, rigid regulations on transfer age as given by the relevant health authorities add on to the challenge. Trial registration number: ISRCTN Registry no 22988897; results (phase I) and pre-results (phase II).